(untitled) (International conference on multidisciplinary science, 2025)
This article discusses the role and importance of psychological preparation in achieving high performance in the sports activities of female basketball players. The main components of psychological preparation—motivation, stress management, self-confidence, team spirit, and concentration—are analyzed. Psychological exercises, training, and modern methods to improve the level of preparation for competitions are discussed. It is also substantiated that psychological preparation has a positive impact on athletes’ emotional stability, strategic thinking, and effective participation in team activities.